The effect of wage subsidies on job retention: Evidence from South Africa during the COVID-19 pandemic - Timothy Köhler; Robert Hill; Haroon Bhorat (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Wage subsidies have served as a primary labour market policy used around the world to mitigate job losses in response to the COVID-19 pandemic. In South Africa, where unemployment is among the highest globally, the Temporary Employer-Employee Relief Scheme supported millions of workers in a far-reaching and progressive manner. We make use of unique labour force panel data to estimate the causal effect of the policy on short-term job retention among formal private sector workers, who represent the majority of workers in the country, by exploiting a temporary institutional eligibility detail and estimating a difference-in-differences model. We find that the policy increased the probability of remaining employed by 16 percentage points in the short-term. This finding holds when subjected to several robustness tests. We further estimate heterogeneous and progressive effects across the wage distribution with larger effects observed for lower-wage workers, against a backdrop of regressively distributed job loss in the country. Our analysis provides evidence on the role of wage subsidies in the mitigation of job loss during crises in developing countries.
Keywords: J08; J38; 330; COVID-19; South Africa; labour market; wage subsidy; job loss; Temporary Employer-Employee Relief Scheme